3m+12=m+36

Simple and best practice solution for 3m+12=m+36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m+12=m+36 equation:


Simplifying
3m + 12 = m + 36

Reorder the terms:
12 + 3m = m + 36

Reorder the terms:
12 + 3m = 36 + m

Solving
12 + 3m = 36 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
12 + 3m + -1m = 36 + m + -1m

Combine like terms: 3m + -1m = 2m
12 + 2m = 36 + m + -1m

Combine like terms: m + -1m = 0
12 + 2m = 36 + 0
12 + 2m = 36

Add '-12' to each side of the equation.
12 + -12 + 2m = 36 + -12

Combine like terms: 12 + -12 = 0
0 + 2m = 36 + -12
2m = 36 + -12

Combine like terms: 36 + -12 = 24
2m = 24

Divide each side by '2'.
m = 12

Simplifying
m = 12

See similar equations:

| aids=9 | | 3+21=74 | | X+2x=-12 | | 2-6=28 | | -37+6m=5m+3(4m+6) | | 6*7+4x=13+4x | | -9-6+12h+40=22 | | -2-6=-5+x | | 12+4v=20 | | 55*x=755-x | | 5+9x=14x | | -7+8x=6x+3 | | 4.7=3.4m-5.5 | | 25+2y=5y+4 | | 0=x^2+8x+225 | | -24+3n=-3(-7n-8)+6n | | 2x^3-16x^2+144=0 | | -.75(x+4)=.2(x-.75) | | x^3-8x^2+72=0 | | -5(x+7)=-35-5x | | -3x+5=7x-25 | | -6(7r+6)=-120 | | 8x+4=24+6x | | 90=-5(-8-5b) | | 11+7m-6-4m= | | 3a-18=2a | | 4n-10=82 | | 4n-10=72 | | -6(1+4b)=6(-4b+8) | | 4n-6=2 | | 4w^2+20w-56=0 | | 5(n-3)=7+3n |

Equations solver categories